1992
DOI: 10.1111/j.1755-3768.1992.tb02087.x
|View full text |Cite
|
Sign up to set email alerts
|

Ophthalmia neonatorum in Northern Norway

Abstract: In a population of 1928 neonates in Northern Norway, ophthalmia neonatorum was diagnosed in 18.9%, including mild and self-limiting cases. Sixteen out of 269 (6.0%) cultured cases were positive for Chlamydia trachomatis. No gonococcal ophthalmia was seen. In neonates whose symptoms began in the maternity wards, the distribution of the isolated microorganisms (mainly Staphylococcus aureus) was different from those in whom symptoms began after discharge (mainly S. aureus, Staphylococcus species (coagulase-negati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2002
2002
2021
2021

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(4 citation statements)
references
References 18 publications
1
3
0
Order By: Relevance
“…The male predominance (60.5% vs 39.5%) was consistent with studies from Iran (62% vs 38%), Norway (75% male neonates) and Saudi Arabia (63% males). 14,21 Sex did not influence the development of ON, which is in agreement with other similar studies. 11,14 There was a relationship between conjunctivitis and neonatal body weight (Table 2).…”
Section: Discussionsupporting
confidence: 93%
“…The male predominance (60.5% vs 39.5%) was consistent with studies from Iran (62% vs 38%), Norway (75% male neonates) and Saudi Arabia (63% males). 14,21 Sex did not influence the development of ON, which is in agreement with other similar studies. 11,14 There was a relationship between conjunctivitis and neonatal body weight (Table 2).…”
Section: Discussionsupporting
confidence: 93%
“…Prior research has suggested that Staphylococcus and Streptococcus were the main pathogens of bacterial conjunctivitis, with Staphylococcus aureus and Streptococcus viridans identified as the most common pathogens in neonatal bacterial conjunctivitis [ 1 , 2 , 12 ]. According to our research, the pattern of bacterial pathogens in neonatal bacterial conjunctivitis in Southern China has changed during the past 15 years.…”
Section: Discussionmentioning
confidence: 99%
“…The infection can be acquired during the passage through the birth canal in vaginal deliveries or from a nosocomial cause due to inappropriate hygiene in the nursery . The aetiology of neonatal conjunctivitis differs between developed countries such as Canada, Israel and the USA and developing countries such as India, Iran and Pakistan . These disparities arise from differences in sanitary conditions in maternity and neonatal wards, environmental conditions, the availability of pregestational and gestational screening, medical prevention, treatment for common sexually transmitted diseases and appropriate medical monitoring and treatment close to delivery .…”
Section: Introductionmentioning
confidence: 99%